Changes in plasma volume and protein concentration induced by cytochalasin E in the rat: A time-course study - Thirayudh Glinsukon (2018)
Cytochalasin E produced a reduction of plasma volume and protein concentration paralleled to biphasic accumulation of peritoneal fluid at 3.0 and 6.75 h after i.p. administration to rats. At the same time, there was an accumulation of fluid in the thoracic cavity following a disappearance of peritoneal fluid in the first peak. Neither a sublethal nor a lethal dose given i.v. induced a similar response. This indicates that such changes caused by cytochalasin E given i.p. may possibly be due to adjustment of the cardiovascular system. © 1982.